2021
DOI: 10.1002/acs.3356
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐order functional observers for descriptor linear time‐invariant systems: a parametric method

Abstract: This article introduces the parametric design method of the reduced-order functional observer for descriptor linear time-invariant systems. First, existence conditions of reduced-order functional observers are provided. Then, based on the solution of generalized Sylvester equations, completely parameterized expressions of the coefficients matrices of the reduced-order functional observer are established, and the design algorithm of the reduced-order functional observer is also proposed. The advantage of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The device that estimates or observes the state variables is called an observer, which has a wide range of applications in dynamic system moni-toring and adjustment, fault detection and separation, identification, and so on [17][18][19][20]. Therefore, many effective methods for analyzing and designing observers and observer-based control strategies have been investigated (see previous studies [21][22][23][24][25][26][27][28][29][30][31][32]). For example, Fernando et al presented a reduced-order observer for nonlinear systems with state-dependent coefficient decomposition and applied to optimal tracking control of linear induction motor [33].…”
Section: Introductionmentioning
confidence: 99%
“…The device that estimates or observes the state variables is called an observer, which has a wide range of applications in dynamic system moni-toring and adjustment, fault detection and separation, identification, and so on [17][18][19][20]. Therefore, many effective methods for analyzing and designing observers and observer-based control strategies have been investigated (see previous studies [21][22][23][24][25][26][27][28][29][30][31][32]). For example, Fernando et al presented a reduced-order observer for nonlinear systems with state-dependent coefficient decomposition and applied to optimal tracking control of linear induction motor [33].…”
Section: Introductionmentioning
confidence: 99%
“…More related research can be found in the literature. [13][14][15][16][17][18][19] Time-delay phenomena are frequently encountered in many practical systems. It has a significant effect on system performance and may cause instability, oscillation, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the above two references, this study presents a solution to the FIO design problem of the LTV system using the parametric design technique. Different from traditional methods, parametric design directly provides all control laws within the system framework, including the freedom parameters, and modifying the free parameters can correspond to changes in the design requirements (Gu et al, 2022c(Gu et al, , 2021bGu and Wang, 2022;Liu et al, 2020Liu et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%